Figure 19. Fossil and recent Catherinum. C–K, N–Q, T, V in Phylogeny of the deep-sea cirripede family Scalpellidae (Crustacea, Thoracica) based on shell capitular plate morphology - Gale, Andrew Scott (Zenodo, 2016)
Figure 19. Fossil and recent Catherinum. C–K, N–Q, T, V, Catherinum anglicum sp. nov., Upper Campanian, Belemnitella mucronata zone, Keswick, Norwich, UK; (O) is the holotype, the other specimens are paratypes. C, D, F, G, carinolatera in external (C, D, F) and internal (G, H) aspects (C, NHMUK IC 1203; D, 1204; F–G, 1206; H, 1208). E, transverse section of carina (NHMUK IC 1205); I, T, dorsal view of carinae (NHMUK IC 1209, 1216); P, lateral view of carina (NHMUK IC 1214); V, internal view of base of carina (NHMUK IC 1217); J, K, O, internal views of scuta, to show large pit for dwarf males (NHMUK IC 1210, 1211, 1213); N, external view of scutum (NHMUK IC 1212); Q, external view of tergum (NHMUK IC 1215). A, B, L, M, R, S, U, Catherinum hispidum (G.O. Sars, 1890). Recent, Norwegian Sea. A, B, carinolatus in external and internal views. L, M, external and internal views of scutum. R, external view of tergum. S, U, dorsal and internal views of carina. Scale bars: S, U, V, 1 mm; A–D, F, G, K–O, Q, R, T, 0.5 mm; E, H, P, 0.2 mm. Published as part of Gale, Andrew Scott, 2016, Phylogeny of the deep-sea cirripede family Scalpellidae (Crustacea, Thoracica) based on shell capitular plate morphology, pp. 266-304 in Zoological Journal of the Linnean Society 176 (2) on page 295, DOI:10.1111/zoj.12321, http://zenodo.org/record/5357812